Numerical Investigation of the Optimum Angle for Open Channel Junction - Waqed H. Hassan; Nidaa Ali Shabat (Salehan Institute of Higher Education, 2023)
Numerous natural and artificial streams, including those for irrigation ditches, wastewater treatment facilities, and conveyance structures for fish movement, have open channel confluences. The flow dynamics at and around the junction are intricate; in particular, immediately downstream of the junction, the flow creates a zone of separation on the inner wall along with secondary recirculation patterns. The structure of this complicated flow depends on several factors, including the flow rates in both channels, the angle of confluence, the geometry of the channels, including the longitudinal slope and bed discordance, the roughness of the boundary, and the intensity of the turbulence. It also has a significant impact on bed erosion, bank scouring, etc. The objective of the current work is to calculate the velocity profile and the separation zone dimensions for four angles (30o, 45o, 60o, and 75o) through the simulation process, and the best angle using a three-dimensional model. This work gives a detailed application of the numerical solution (Finite Volume) via Flow 3D software. Results for two flow discharge ratios, q*=0.250 and q*=0.750 were shown; the numerical model and the experimental results agreed well. The findings are consistent with past research and demonstrate how the main channel flow pattern is affected by changes in the channel crossing angle, as well as how greater separation zones are produced in the main channel when the flow discharge ratio q* (main channel flow divided by total flow) is smaller. Analysis revealed that the separation zone's smallest diameter will be at the 75ocrossing angle. Doi: 10.28991/CEJ-2023-09-05-07 Full Text: PDF